Cloning, Heterologous Expression, and Characterization of a βκ-Carrageenase From Marine Bacterium Wenyingzhuangia funcanilytica: A Specific Enzyme for the Hybrid Carrageenan–Furcellaran - Cao, Siqi; Zhang, Yuying; Chen, Guangning; Shen, Jingjing; Han, Jin; Chang, Yaoguang; Xiao, Hang; Xue, Changhu (Frontiers in Microbiology, 2021)
Carrageenan is a group of important food polysaccharides with high structural heterogeneity. Furcellaran is a typical hybrid carrageenan, which contains the structure consisted of alternative β-carrageenan and κ-carrageenan motifs. Although several furcellaran-hydrolyzing enzymes have been characterized, their specificity for the glycosidic linkage was still unclear. In this study, we cloned, expressed, and characterized a novel GH16_13 furcellaran-hydrolyzing enzyme Cgbk16A_Wf from the marine bacterium Wenyingzhuangia fucanilytica CZ1127. Cgbk16A_Wf exhibited its maximum activity at 45 °C and pH 6.0, and showed high thermal stability. The oligosaccharides in enzymatic products were identified by liquid chromatography coupled with high resolution mass spectrometry (LC-HRMS) and nuclear magnetic resonance (NMR). It was confirmed that the Cgbk16A_Wf specifically cleaves the β-1,4 linkages between β-carrageenan and κ-carrageenan from non-reducing end to reducing end. Considering the structural heterogeneity of carrageenan and for the unambiguous indication of the specificity, we recommended to name the furcellaran-hydrolyzing activity represented by Cgbk16A as “βκ-carrageenase” instead of “furcellaranase”.